Spatial and temporal variability of the extent of chemically processed stratospheric air - Kaye, Jack A.; Douglass, Anne R.; Rood, Richard B.; Stolarksi, Richard S.; Newman, Paul A. (1991)
Simulations of the spatial and temporal variability of the extent of chemically processed air in the Arctic stratosphere have been carried out using a three-dimensional chemistry-transport model for the winters of 1979 and 1989. Chemically processed air is identified in the model as that in which the amounts of hydrogen chloride (HCl) calculated with parameterized loss for conditions appropriate to polar stratospheric cloud (PSC) formation are substantially smaller than those calculated in a model with gas phase chemistry only. It is seen that chemically processed air may be identified over much of the Arctic lower stratosphere from early January to late February, with HCl depletions being larger in 1989 than in 1979. Near the latitude of the Arctic circle, there is important spatial and temporal variability in the extent of chemically processed air. There is some evidence for transport to midlatitudes of processed air during these winters, but the HCl reductions are much smaller and more sporadic than those near the pole. At 62 and 42N, processed air is calculated to occur preferentially over the longitude regions from 60-120E and 270-330E.